2015
DOI: 10.1016/j.taap.2015.07.011
|View full text |Cite|
|
Sign up to set email alerts
|

Malignant human cell transformation of Marcellus Shale gas drilling flow back water

Abstract: The rapid development of high-volume horizontal hydraulic fracturing for mining natural gas from shale has posed potential impacts on human health and biodiversity. The produced flow back waters after hydraulic stimulation is known to carry high levels of saline and total dissolved solids. To understand the toxicity and potential carcinogenic effects of these waste waters, flow back water from five Marcellus hydraulic fracturing oil and gas wells were analyzed. The physicochemical nature of these samples was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the context of shale gas, the situation is even more complex as the use of chemicals in hydraulic fracturing of the argillaceous host rocks has raised strong public concerns on health effects, both of flowback water spills and leaks to surface water or groundwater resources and of stray gas. [64,65]. Much effort is put into optimizing water and groundwater monitoring [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of shale gas, the situation is even more complex as the use of chemicals in hydraulic fracturing of the argillaceous host rocks has raised strong public concerns on health effects, both of flowback water spills and leaks to surface water or groundwater resources and of stray gas. [64,65]. Much effort is put into optimizing water and groundwater monitoring [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…An experimental study on the carcinogenicity of hydraulic fracturing wastewater observed that immortalized human bronchial epithelial cells exposed to flowback water collected from unconventional natural gas drilling of the Marcellus Shale underwent malignant transformation and exhibited altered morphology compared to parental cells (Yao et al, 2015). The flowback water sample contained relatively high concentrations of barium and strontium.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, as these articles cite many of the "Animal-Focused Articles" listed above as supporting evidence. For instance, studies show that chemicals used in hydraulic fracturing pose a risk to ecosystems (Entrekin et al 2018;He et al 2017;Loh and Loh 2016;Vandecasteele et al 2015;Yao et al 2015). Specifically, Kassotis et al (2016b) find that injection well disposal sites reveal elevated levels of toxins that could disrupt reproduction and development in aquatic animals (see, e.g., Elliott et al 2017).…”
Section: Animal-observant Articlesmentioning
confidence: 99%